Characterization of Casein Fractions from Algerian Dromedary (Camelus dromedarius) Milk - Alim, Naima; Fondrini, Fabio; Bonizzi, Ivan; Feligini, Maria; Enne, Giuseppe (Pakistan Journal of Nutrition, 2005)
To characterize casein fractions in Algerian dromedary`s milk, samples from two breeds, Larbaa and Targui, were analyzed using electrophoretic and chromatographic techniques. Analysis performed by isoelectric focusing showed heterogeneity within the same breed and between the breeds. Some samples featured a reduced beta-lactoglobulin content and one sample from Larbaa breed showed the lack of bands in the most acidic region, where kappa-casein focuses. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of this sample allowed identifying the alphas1-, alphas2- and beta-casein fractions only. High performance liquid chromatography analysis of precipitated casein showed three main peaks. In order to characterize them, electrospray ionization-mass spectrometry was exploited. Their measured molecular masses were 24,760, 22,060 and 24,970, corresponding to alphas1-, alphas2- and beta-casein. Analytical results suggested the absence of kappa-casein in this sample. Nevertheless, investigations at DNA level are necessary in order to better characterize kappa-casein locus in Larbaa breed and to define this species`s milk peculiar properties.